Laymen's Narratives in Amouddou's Eco-documentary: An Ecolinguistic Analysis - Mohamed Mliless; Lamiae Azzouzi; Saida Hdii; Handoko Handoko (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
Documentary films, generally of short or medium-length, have informative and educational purposes. They present authentic reports on areas of life, human activities, and the natural world. Particularly, eco-documentaries aim to raise environmental awareness towards the degradation of natural elements; they present alternatives for environmental issues such as pollution, global warming, and deforestation. To reinforce the argumentative process of environmental documentaries, laymen discourse contributes a lot to the meaning-making of productions. Within the framework of discourse analysis and ecolinguistics, this work examines fear and threat expressions used by ordinary witnesses to reinforce argumentation in Lahoucine Faouzi's eco-documentary entitled